Cerebral structural alterations in the patients undergoing postherpetic neuralgia: A VBM–MRI study - Li Niu; Yi Hu; Cheng‐Dong Yuan; Xing‐Yan Wu; Lei‐Lei Zheng; Yi Zhang (Ibrain, 2022)
Abstract This study aimed to investigate the changes in gray matter (GM) volume and density in patients with postherpetic neuralgia (PHN). Using voxel‐based morphometry (VBM), the differences in cerebral GM volume and concentration between 25 PHN patients and 25 healthy controls with similar gender ratios, ages, and education were compared. Meanwhile, correlation analysis was performed between the value of GM volume/concentration in the brain areas with discrepancy and the visual analog scale (VAS) score/lesion duration. The global GM volume in PHN patients was lower than that of healthy controls, while the total volume of cerebrospinal fluid in PHN patients was higher than that of healthy controls. In PHN patients, the GM volume decreased in the striatum, cerebellum, precentral gyrus, middle frontal gyrus, parahippocampal gyrus, postcentral gyrus, and so forth; the GM concentration decreased in the striatum, insula, middle and posterior cingulate, and superior temporal gyrus. There was a negative correlation between GM concentration in the right parahippocampal gyrus and the VAS in patients with PHN. In PHN patients, GM volume and density in the brain regions involved in nociceptive sensation, pain perception, and integration decreased significantly. The interaction between chronic pain of PHN and alteration of the cerebral structure may contribute to the occurrence and development of PHN.